THE VALUE OF ANTIPHOSPHOLIPID ANTIBODIES CIRCULATION IN WOMEN WITH AUTOIMMUNE DISEASES OF THYROID GLAND AND MISCARRIAGE IN HISTORY - S. A. Alieva; M. A. Odamanova; S. Z. Allakhkulieva; T. Kh. Khashaeva (IRBIS LLC, 2016)
In the world literature many works which main object of studying are women with repeated miscarriage and infertile women after IVF are published. Majority of these researches demonstrated significant association between the circulation of thyroid autoantibodies, infertility and high risk of fetal loss. Adequate level of thyroid hormones is necessity for normal functioning of reproductive system. In this article the association of miscarriage and autoimmune diseases of thyroid gland is considered. This association arose not incidentally perhaps the mechanism of such interrelation is that fact that existence of antibodies reflects the general activation of immune system and increases autoimmune process against feto-placental system. Objective: to investigate spectrum of antiphospholipid antibodies in patients with various forms of autoimmune thyroid disease and a history of recurrent pregnancy loss. Materials and Methods: 154 women were involved including 112 women with autoimmune thyroid disease (Graves' disease, autoimmune thyroiditis, postpartum thyroiditis) and 42 with miscarriage history, but without thyroid disease. Results: there is no significant difference between the frequency of detection of antiphospholipid syndrome (APS) among women with ATD and without ATD and with anamnesis of miscarriage. However, APS most often detected in patients with thyrotoxicosis (45%; p <0.005). High incidence of APS among women with autoimmune thyroiditis (33.33%) also identified. Conclusion: check up of thyroid status for all pregnant women with increased thyroid function could be recommended. Early detection and correction of the hemostatic system and thyroid dysfunction during pregnancy will help to prevent complications.